2019
DOI: 10.1094/pdis-05-18-0763-re
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characteristics and Control Efficacy of a Novel SDHI Fungicide Pydiflumetofen Against Sclerotinia sclerotiorum

Abstract: Pydiflumetofen is a novel succinate dehydrogenase inhibitor fungicide. In the current research, we determined the sensitivity of 166 Sclerotinia sclerotiorum strains to pydiflumetofen using mycelial growth inhibition method. The results suggest that pydiflumetofen exhibited a strong inhibitory activity against S. sclerotiorum and the EC50 values ranged from 0.0058 to 0.0953 μg ml−1, with a mean EC50 value of 0.0250 μg ml−1. However, the baseline sensitivity was not normally distributed because of a high variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Previous studies reported that SDHIs have good effects in the prevention and control of other diseases. For example, pydiflumetofen can effectively inhibit Sclerotinia sclerotiorum , with an average EC 50 value of 0.0250 μg/mL [18]. In addition, boscalid and isopyrazam have a better inhibitory effect on mycelial growth of Aspergillus flavus than Fusarium species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that SDHIs have good effects in the prevention and control of other diseases. For example, pydiflumetofen can effectively inhibit Sclerotinia sclerotiorum , with an average EC 50 value of 0.0250 μg/mL [18]. In addition, boscalid and isopyrazam have a better inhibitory effect on mycelial growth of Aspergillus flavus than Fusarium species.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the newly developed fungicides are based on the original reactive group as a backbone. At present, SDHIs have been widely applied for controlling many plant diseases [15,16,17,18]. However, SDHIs are rarely used to control FHB, especially in the control of DON production in wheat grains.…”
Section: Introductionmentioning
confidence: 99%
“…Pydiflumetofen has been registered for use in potatoes, soybean, oilseed rape, grapes and peanuts. 4,23 Owing to its excellent efficacy against FHB, pydiflumetofen has been, since 2019, launched into the market in China to control wheat FHB. To date, however, no data is available regarding the potential pyd-resistance selected in F. asiaticum, or any reports of resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The N‐methoxy group of SDHIs possesses a unique broad spectrum across many crops and diseases. Pydiflumetofen has been registered for use in potatoes, soybean, oilseed rape, grapes and peanuts 4,23 . Owing to its excellent efficacy against FHB, pydiflumetofen has been, since 2019, launched into the market in China to control wheat FHB.…”
Section: Introductionmentioning
confidence: 99%
“…S1) is a novel SDHI chiral fungicide that has high efficiency and broad-spectrum bioactivity. For example, a few studies 18,19 have reported that pydiflumetofen exhibited strong inhibitory activity against Sclerotinia sclerotiorum with a mean EC 50 value of 0.0250 μg mL −1 . Neves et al 20 established the baseline sensitivity of Cercospora zeae-maydis with a mean EC 50 value of 0.0040 μg mL −1 , and Hou et al 21 established the baseline sensitivities of Fusarium asiaticum with a mean EC 50 value of 0.0745 μg mL −1 .…”
Section: Introductionmentioning
confidence: 99%